TINJAUAN YURIDIS PENINJAUAN KEMBALI LEBIH DARI SEKALI DIKAITKAN DENGAN UPAYA PERLINDUNGAN TERHADAP HAK TERPIDANA BERDASARKAN SURAT EDARAN MAHKAMAH AGUNG NOMOR 7 TAHUN 2014 TENTANG PENGAJUAN PERMOHONAN PENINJAUAN KEMBALI DALAM PERKARA PIDANA - Situmeang, Melisa; Indra, Mexsasai; ', Erdiansyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Reconsideration is a remedy that can be taken by the convict in a case of law against a decision of a court that has permanent legal force in the judicial system in Indonesia . Reconsideration categorized as an extraordinary legal remedy because it has the privilege, meaning that it can be used to reopen a court decision which has had permanent legal force. Thus the institution Reconsideration is a remedy that is used to retract or reject the judge's decision has had permanent legal force. Mary Jane Veloso a drug kingpin arrested for carrying 2.6 kg of heroin in Yogyakarta, on March 25, 2015 Mary Jane file a judicial review through the Sleman District Court but was rejected. However, the Review that Mary Jane make a schedule execution pending death. Then, Mary Jane file a Reconsideration second, but immediately rejected. The reason for rejection of the Supreme Court because it does not find new Novum.This type of research is classified in normative law research using the method of assessment literature or documentary study, the author quotes from books, literature, or book support, which has links with the problems to be studied. The data used primary legal materials, secondary law and tertiary legal materials.From the research problem there are five things that can be inferred. First, provisions prohibiting judicial review more than once not only found in the Code of Criminal Procedure but also in other regulations such as the Law on Judicial Power and the Law on the Supreme Court. second, a growing number of reconsideration is granted by the Supreme court, indicates that the court decision a lot wrong, make mistakes and wrong. Third, for reasons of legal certainty and justice. Fourth, the absence of restrictions on the filing of a judicial review will have implications for the possibility of flooding case reconsideration . Fifth, Novum Ideal requirements that can be submitted as evidence in a judicial review more than once that the new witnesses, new information, new evidence, a major role of judges, and should be tolled in the legislation.Suggestions author, the terms of the petition filing Reconsideration should be clarified, so as not to cause more mistakes than those who want to apply for a judicial review and determine the qualifications Novum described in detail with examples Novum-novum or new circumstances in the verdict Reconsideration ,Keywords: Reconsideration - Convicts Rights - Supreme Court Circular